Marinos Koutsomichalis - Koutsomichalis, Marinos (My University, 2020)
Conceived and co-organised by Emma Cocker, Alexander Damianisch, Cordula Daus and Lena Séraphin, this Society of Artistic Research Special Interest Group (SAR SIG) provides contexts for coming together via the exchange of language-based research. The intent is to support developments in the field of expanded language-based practices by inviting attention, time and space for enabling understanding of/and via these practices anew.